Forecasting of Cotton Yield with Fuzzy Information - D T, Mukhamedieva; X.A, Primova; R.T, Raximov (International Journal of Engineering and Technology, 2018)
The models of cotton yield forecasting using methods of fuzzy mathematics are considered. In the paper, the economic system as a human-centered, realistic multiagent system characterized by incompleteness and partial reliability of information is considered. Representation of the behavior of economic agents in our approach is based on fuzzy logic and is given by inaccurate constraints.Â Â